Diversity and ecological structure of vibrios in benthic and pelagic habitats along a latitudinal gradient in the Southwest Atlantic Ocean - Luciane A. Chimetto Tonon; Bruno Sergio de O. Silva; Ana Paula B. Moreira; Cecilia Valle; Nelson Alves Jr; Giselle Cavalcanti; Gizele Garcia; Rubens M. Lopes; Ronaldo B. Francini-Filho; Rodrigo L. de Moura; Cristiane C. Thompson; Fabiano L. Thompson (PeerJ, 2015)
We analyzed the diversity and population structure of the 775 Vibrio isolates from different locations of the southwestern Atlantic Ocean (SAO), including St. Peter and St. Paul Archipelago (SPSPA), Abrolhos Bank (AB) and the St. Sebastian region (SS), between 2005 and 2010. In this study, 195 novel isolates, obtained from seawater and major benthic organisms (rhodoliths and corals), were compared with a collection of 580 isolates previously characterized (available at www.taxvibrio.lncc.br). The isolates were distributed in 8 major habitat spectra according to AdaptML analysis on the basis of pyrH phylogenetic reconstruction and ecological information, such as isolation source (i.e., corals: Madracis decactis, Mussismilia braziliensis, M. hispida, Phyllogorgia dilatata, Scolymia wellsi; zoanthids: Palythoa caribaeorum, P. variabilis and Zoanthus solanderi; fireworm: Hermodice carunculata; rhodolith; water and sediment) and sampling site regions (SPSPA, AB and SS). Ecologically distinct groups were discerned through AdaptML, which finds phylogenetic groups that are significantly different in their spectra of habitat preferences. Some habitat spectra suggested ecological specialization, with habitat spectra 2, 3, and 4 corresponding to specialization on SPSPA, AB, and SS, respectively. This match between habitat and location may reflect a minor exchange of Vibrio populations between geographically isolated benthic systems. Moreover, we found several widespread Vibrio species predominantly from water column, and different populations of a single Vibrio species from H. carunculata in ecologically distinct groups (H-1 and H-8 respectively). On the other hand, AdaptML detected phylogenetic groups that are found in both the benthos and in open water. The ecological grouping observed suggests dispersal and connectivity between the benthic and pelagic systems in AB. This study is a first attempt to characterize the biogeographic distribution of vibrios in both seawater and several benthic hosts in the SAO. The benthopelagic coupling observed here stands out the importance of vibrios in the global ocean health.